Cytoreduction plus hyperthermic intraperitoneal chemotherapy for peritoneal carcinomatosis in colorectal cancer patients: a single-center cohort study - Solaini, Leonardo (World J Surg Oncol, 2019)
BACKGROUND: In this study, we report our experience of cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) in patients with peritoneal carcinomatosis (PC) from colorectal cancer (CRC), focusing on the factors affecting survival. METHODS: All patients with surgically treated PC from colorectal cancer and with no involvement of other organs referred to our institute from March 2005 to December 2017 were included in the analysis. RESULTS: Thirty-eight patients underwent CRS-HIPEC, and all had a completeness of cytoreduction score of 0 (CC0). The median operating time was 645 min (interquartile range [IQR] 565–710). Five patients (13.1%) had Clavien-Dindo grade > 2 postoperative complications. Median overall survival (OS) was 60 months. In the Cox regression for OS, calculated on the CRS-HIPEC group, the peritoneal cancer index (PCI) > 6 (hazard ratio [HR] 4.48, IQR 1.68–11.9, P = 0.003) and significant nodal involvement (N2) (HR 3.89, IQR 1.50–10.1, P = 0.005) were independent prognostic factors. Median disease-free survival (DFS) was 16 months. Only N2 (HR 2.44, IQR 1.11–5.36, P = 0.027) was a significantly negative prognostic factor for DFS in multivariate analysis. CONCLUSIONS: CRS-HIPEC can substantially improve survival. However, patients with high PCI (PCI > 6) and significant nodal involvement (N2) may not benefit from the procedure.